Cultural heritage building's pathology in Lima Historic Center. Humidity, causes and consecuences - Berenguel Paredes, Ana Elisa (2018)
The conservation of cultural heritage buildings is a complex process that must begin with the complete knowledge of the objet to conserve. This Knowledge includes the identification of values, qualities, constructive characteristics and the real situation of the building. To known the real situation, means to identify the damages, the visible effects of the problems, analyzing the causes and control the consequences.Pathological processes in cultural heritage buildings, are really different, depending on shapes, constructive materials, orientation, etc, but, humidity, in every different ways, is without doubts, the biggest problem that cultural heritage buildings have to face, and it is considered equal than disinterestedness on cultural heritage conservation.Atmospherically conditions, pipe lines in bad shape, interventions without technical points of view, becomes the worst enemies of cultural heritage buildings, because of many serious consequences, like the appearance of new damages; increased with bad solutions than only cover the effects, without finding and canceling the causes.